Health insurance coverage and maternal healthcare services utilization in Jordan: evidence from the 2017-18 Jordan demographic and health survey - Petula Fernandes; Emmanuel Kolawole Odusina; Bright Opoku Ahinkorah; Komlan Kota; Sanni Yaya (BMC, 2021)
Abstract Background Despite the relationship between health insurance coverage and maternal healthcare services utilization, previous studies in Jordan on the use of maternal healthcare services have mainly focused on patterns and determinants of maternal healthcare services utilization in Jordan. Therefore, this study investigated the relationship between health insurance coverage and maternal healthcare services utilization in Jordan. Methods This study used secondary data published in 2017-18 Jordan Demographic and Health Survey on 4656 women of reproductive age (15-49 years). The independent variable was health insurance coverage and the outcome variable was maternal healthcare services utilization, measured through timing of first antenatal visit, four or more antenatal care visits, and skilled birth attendance. The data were analyzed using descriptive statistics and binary logistic regression. Results Out of the total number of women who participated in the study, 38.2% were not covered by health insurance. With maternal healthcare utilization, 12.5%, 23.2%, and 10.1% respectively, failed to make early first antenatal care visit, complete four or more antenatal care visits and have their delivery attended by a skilled worker. After controlling for the socio-demographic factors, health insurance coverage was associated with increased odds of early timing of first antenatal care visits and completion of four or more antenatal care visits (aOR = 1.33, p < 0.05, aOR = 1.25, p < 0.01, respectively). However, women who were covered by health insurance were less likely to use skilled birth attendance during delivery (aOR = 0.72 p < 0.001). Conclusions Jordanian women with health insurance coverage were more likely to have early first antenatal care visits and complete four or more antenatal care visits. However, they were less likely to have their delivery attended by a skilled professional. This study provides evidence that health insurance coverage has contributed to increased maternal healthcare services utilization, only in terms of number and timing of antenatal care visits in Jordan. It is recommended that policy makers in Jordan should strengthen the coverage of health insurance in the country, especially among women of reproductive age in order to enhance the use of maternal healthcare services in the country.